2011
DOI: 10.1111/j.1540-8159.2011.03075.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Right Ventricular Pacing with Advanced Atrioventricular Search Hysteresis: Results of the PREVENT Study

Abstract: The enhanced AVSH algorithm reduces %VP compared with standard AVSH in patients with intermittent AV block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The feasibility of algorithms designed to decrease the burden of unnecessary ventricular pacing has been demonstrated in patients with dual-chamber pacemakers [36][37][38]. These algorithms usually provide functional AAI pacing with monitoring of atrioventricular conduction and an automatic mode switch from AAI to DDD during episodes of atrioventricular block.…”
Section: Non-crt Devices: Algorithms To Reduce Right Ventricular Stimmentioning
confidence: 99%
“…The feasibility of algorithms designed to decrease the burden of unnecessary ventricular pacing has been demonstrated in patients with dual-chamber pacemakers [36][37][38]. These algorithms usually provide functional AAI pacing with monitoring of atrioventricular conduction and an automatic mode switch from AAI to DDD during episodes of atrioventricular block.…”
Section: Non-crt Devices: Algorithms To Reduce Right Ventricular Stimmentioning
confidence: 99%
“…This study was a prespecified subanalysis from the PREVENT (Philos AV Repetitive Hysteresis: Effect on Ventricular Pacing) multicenter, randomized, crossover study. As reported previously, PREVENT compared VP% intraindividually for (1) the fixed, rate‐independent, moderately prolonged AV delay of 225 ms; (2) standard AVSH; and (3) enhanced AVSH with two new features described in the following section.…”
Section: Methodsmentioning
confidence: 91%
“…Major exclusion criteria were permanent AV block of any degree, persistent supraventricular tachyarrhythmia, neurocardiogenic syncope, pregnancy, or mental disability. Further details on patient selection can be found in the previous report . The study was approved by the ethics committee of the medical faculty of the Technical University, Munich, Germany (project number 1282/05).…”
Section: Methodsmentioning
confidence: 99%
“…Early studies in patients with sick sinus syndrome and paroxysmal AF suggested that atrial-based pacing in and of itself might prevent AF by reducing the incidence of bradycardia-induced atrial fibrillation [6]. Atrial-based pacing has been shown to be superior to ventricular based pacing in the prevention of AF [7,8]. Pacing algorithms have evolved to minimize right ventricular pacing in patients with sick sinus syndrome and intact atrioventricular conduction.…”
Section: Introductionmentioning
confidence: 99%